Pematahan Dormansi Teknis dan Komposisi Media Semai Pada Pembibitan Tanaman Kacang Sacha Ichi (Plukenetia volubilis L.): Pematahan Dormansi Teknis dan Komposisi Media Semai Pada Pembibitan Tanaman Kacang Sacha Ichi (Plukenetia volubilis L.) - Fitriyah, Nur; Irawati, Titik; Rahmatika, Widyana; Amanda, Neha (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2025)
Sacha inchi (Plukenetia volubilis L.) is one of the underutilized crops that has been adopted as a food source due to its high nutritional value, which is gradually being recognized as having potential benefits for human health. An initial obstacle to the cultivation of this commodity is seed dormancy, which requires a solution. The objectives of this study are 1) to determine the first count and final count in testing the germination capacity of seeds and suitable germination media. A completely randomized design (CRD) factorial was selected for this study. Factor 1 was P1 (ordinary water), P2 (water at 50 °C), P3 (water at 80 °C), and factor. 2 was M1 = soil:compost (2:1), M2 = soil: Sand (2:1), M3 = Soil:Sand:Compost (2:1:1). Each combination was repeated three times, with each combination consisting of 4 polybags, totaling have 135 polybags. Data were analyzed using F-tests with analysis of variance (ANOVA). If a significant effect was observed, a BNT test (5%) was conducted. Based on the research conducted, there was no significant interaction effect between seed soaking techniques and planting medium composition on germination observation. Breaking dormancy using different water immersion temperatures affects plant height at 21 days after sowing (DAS) and the number of leaves at 7 DAS. 3. Growing medium treatment has a significant effect on the number of leaves, and the M3 medium (soil : sand : compost) shows a significantly better effect compared to the l treatment.